2015
DOI: 10.1089/dia.2014.0296
|View full text |Cite
|
Sign up to set email alerts
|

Web-Based Remote Monitoring Systems for Self-Managing Type 2 Diabetes: A Systematic Review

Abstract: This systematic review aims to evaluate evidence for viability and impact of Web-based telemonitoring for managing type 2 diabetes mellitus. A review protocol included searching Medline, EMBASE, CINAHL, AMED, the Cochrane Library, and PubMed using the following terms: telemonitoring, type 2 diabetes mellitus, self-management, and web-based Internet solutions. The technology used, trial design, quality of life measures, and the glycated hemoglobin (HbA1c) levels were extracted. This review identified 426 public… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 38 publications
2
30
1
1
Order By: Relevance
“…The Gather system, built on behavioral change theories to support self-management and to improve communication with physicians, resulted in improved A1c levels, similar to an earlier study reported by Shetty et al [10]. A systematic review on web-based remote monitoring systems in the self-management of type 2 diabetes concluded that there is complexity involved in the technology as well as in its implementation [11]. These must be addressed.…”
supporting
confidence: 55%
“…The Gather system, built on behavioral change theories to support self-management and to improve communication with physicians, resulted in improved A1c levels, similar to an earlier study reported by Shetty et al [10]. A systematic review on web-based remote monitoring systems in the self-management of type 2 diabetes concluded that there is complexity involved in the technology as well as in its implementation [11]. These must be addressed.…”
supporting
confidence: 55%
“…Several systematic reviews evaluated the potential benefits of information technology–based diabetes management interventions, and all concluded that information technology–based interventions could improve diabetes management for adult care [7-11]. However, they did not extend their focus to consider blood glucose measurements using meta-analysis techniques or map interventions incorporating CCM elements.…”
Section: Introductionmentioning
confidence: 99%
“…Several approaches have been reported in the literature that is available on setting-up a telemedicine service to support patients at home (9,15,16). They differ from one medical discipline to another by using different methods and tools.…”
Section: Discussionmentioning
confidence: 99%
“…Remote monitoring in CHF patient management may have a significant protective clinical effect on patients in comparison with those receiving regular care (7). Similarly, studies of remote monitoring in DM2 patients show positive effects e.g.an improvement (lowering) in HbA1c levels (8,9). JaVno ZdraVstVo (VarstVo pri deLu) …”
Section: Introductionmentioning
confidence: 97%